DIMENSI-DIMENSI GAYA HIDUP KONSUMTIF PADA REMAJA - Irma Pamungkas; Tri Na'imah (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The systematic aim of this review is to synthesize the dimensions of the consumptive lifestyle from various previous studies. This literature study was carried out by reviewing 20 articles originating from Taylor and Francis database sources, Semantic Schoolar, SAGE, and SSRN Electronic Journal. The author uses PICOSS (Population, Intervention, Comparators, Outcome Variable, Study Design, and Setting) to filter out some inclusion and exclusion criteria. Then the results of the 20 journals show that the dimensions of a consumptive lifestyle consist of environment, technology, other cultural influences, family, competition, going with the flow, prestige, objects as self-expression, objects of consumption as hyper-reality media and substitutes for pleasure, having pleasure in excessive luxury, waste of money, action so that its existence continues to be recognized, modernization of lifestyle patterns, setting beauty standards, and symbols of confidence